Mobile phone accessibility values for users with disabilities. (2013) - Mak, Brenda; Beckman, Paul; Bohn, Nicole
In May 2008, the Convention on the Rights of Persons with Disabilities came into force. Its passage requires countries to review policies and regulations on the accessibility of Information and Communication Technology (ICT). Improvements in technology have enabled providers and manufacturers to enhance the accessibility features of mobile phones, but there is a need to conduct surveys among users with disabilities to find out the perceived accessibility values of mobile phones (ITU, 2012, p.62). This study examines the relationships among accessibility values, technostress, and switching intentions for mobile phone users with disabilities. A survey was conducted and a structural equation model was developed. The latent construct of Accessibility Value, observed in terms of Usability, Connection and Companionship, has a direct and marginal negative effect on Switching Intention, and an indirect significant negative effect on Switching Intention through Technostress . Implications for enhancing the accessibility of mobile phones are discussed.